Financial And Current Account Interrelationship : An Empirical Test - Lau, Evan; FU, Nelson (ASERS Publishing, 2011)
Theoretically, financial account (FA) serves as a means of financing deficit in a country’s current account (CA). With the outburst of the rapid globalization and the liberalization of the capital markets, the function of FA could be a major cause of CA instability. This study empirically investigates the interrelationship between CA and the components of FA for the four crisis-affected Asian countries of Indonesia, Korea, the Philippines and Thailand. Empirical results show that deficit in CA mirror the surplus in FA supporting the theoretical foundation of balance of payment (BOP). We observed CA Granger causes FA suggesting that CA can be used as the control policy variable for the flows of capital in these countries. Therefore, the innovation of CA (whether deficit or surplus) would be important information for the liberalization and globalization of FA.